Pemerolehan Bahasa Arab Pada Murid RA Al-Jannah Koto Majidin Berdasarkan Perspektif Vygotsky - Berliani, Denitia; Jailani, Muhammad; Wargadinata, Wildana (Program Studi Pendidikan Bahasa Arab, 2024)
The purpose of this study is to explain how words in Arabic are learned by students of RA Al-Jannah Koto Majidin based on Vygotsky’s perspective. This study employs a qualitative research design utilizing descriptive analysis. The sample of this research consisted of 2 male students and 3 female students who were randomly selected (probability sampling). The result are the acquisition of Arabic words in student of RA Al-Jannah Koto Majidin based on Vygotsky’s theory consisting of 5 concepts related to early childhood cognitive development namely: (1) zone of proximal development, student are still unable to acquire Arabic words independently; (2) scaffolding, students get help from teachers and peers who are more capable; (3) language and thoughts, students will repeat the vocabulary they have learned; (4) cooperative learning, students will cooperate (cooperative) in solving the questions given by the teacher; (5) giving examples to each other, the teacher gives concrete examples to students regarding the vocabulary being studied.